Law in God’s Law - Gałkowski, Tomasz (Philosophy and Canon Law, 2024)
The concept of God’s law is rooted in theology and canon law. However, the content expressed by this concept is very extensive. In addition, this concept is replaced by many others indicating the proper content for them. Therefore, the usefulness of the concept of divine law remains questionable. The author of the study expresses the opinion that the concept of law and the reality expressed by it are not adequate to properly grasp the meaning of the concept of God’s law. The consideration of law in God’s law should be carried out in the symbiosis of faith and reason, the acceptance of God’s will and its expression in the appropriate way of realizing the ecclesiastical form of the Christian religion.